Is European Fund’s implementation subject to slipup for emerging countries’ approach? (International Journal of Business Innovation, 2023)
Our study explores in a holistic approach the topic of non-refundable European funds (NREF). Taking as pillars the results of the operational audit (weakness and errors) and the remedial role of follow-up operations, we approach in a longitudinal manner (2008-2020) the evolution of the European funds in the case of Romania, a former communist country, member of the EU. Through a theoretical and empirical framework, our results show a fluctuating evolution on all the operational programmes implemented in Romania over 22 years. The results can be a reference base for Est European countries’ experience, newly acquainted with EF. The unveiled results can be justified by the Romania’s government lack of experience, fluctuating legislation, minor knowledge of the Eastern European culture by EU, aspects that, in recent years, based on a better familiarity with the non-reimbursable funds and the effects of follow-up operations, are significantly improving.
Keywords: External audit; Non-refundable European funds (NREF); Romania; Irregularities; Longitudinal